LKPD Berbasis Problem Based Learning: Upaya Mendukung Peningkatan Keterampilan Berpikir Kritis Siswa pada Materi Momentum Impuls, dan Tumbukan - aisyah, siti aisyah (Balai Diklat Keagamaan Surabaya, 2025)
The purpose of this research is to develop the valid, practical, and effective of student worksheet base on Problem-Based Learning (PBl) to enhance students' critical thinking skills. The development of student worksheet based on PBL refers to the Dick and Carey model, which has been modified according to specific needs. The subjects of this study were 10th-grade students.. The worksheet development process followed several main stages, including identification, analysis, design, development, validation, implementation, and evaluation. The results of the worksheet implementation showed a significant improvement in students' critical thinking skills. The pre-test score was 20.18%, while the post-test score increased to 91.48%. These findings indicate that the use of student worksheet based on PBL effectively enhanced students' critical thinking skills.